Green turtle diet is dominated by seagrass in the Western Indian Ocean except amongst gravid females - Stokes, Holly J.; Mortimer, Jeanne A.; Hays, Graeme C.; Unsworth, Richard K. F.; Laloë, Jacques-Olivier; Esteban, Nicole (Marine biology, 2019)
Green turtles ( Chelonia mydas ) are key herbivores of tropical and subtropical neritic habitats and play a major role in structuring seagrass meadows. We present the first detailed assessment of green turtle diet in the Western Indian Ocean using the gut contents of salvaged animals from three atolls in the Republic of Seychelles separated from each other by 400–825 km: Cosmoledo (adults, n = 12), Farquhar (adults, n = 33; immature, n = 1) collected in 1982–1983; and Desroches (immatures, n = 8) in 2016–2018. We report the first comparison of the diets of gravid females ( n = 17), males ( n = 26) and non-breeding females ( n = 2) at sites providing both foraging and breeding habitat. Seagrass (mostly Thalassodendron ciliatum ) dominated the diet, accounting for 95% of the mean gut content biomass for males and non-breeding females but only 58% for gravid females, alongside relatively large amounts of substrate (14%) and macroalgae (13%). Satellite tracking of post-nesting green turtles from Chagos Archipelago in 2016 located foraging sites at Farquhar Atoll that coincided with capture locations of 26 of the 33 adult turtles sampled there in 1983. In situ surveys of those sites in 2018 revealed extensive nearly monospecific beds of T. ciliatum. The prominence of seagrass in the diet of green turtles and connectivity between foraging and nesting habitats throughout the region illustrate the need to conserve and monitor seagrass habitats of the Western Indian Ocean especially in the context of changing green turtle population densities.